2009
DOI: 10.1080/02640410802578172
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fat oxidation during exercise in obese pubertal boys: Clinical implications

Abstract: In this study, we examined fat oxidation rates during exercise in obese pubescent boys. Three groups of pubescent boys (16 pre-pubescent, Tanner's stage I; 16 pubescent, Tanner's stage III; and 14 post-pubescent, Tanner's stage V) performed a graded test on a leg cycle ergometer. The first step of the test was fixed at 30 W and power was gradually increased by 20 W every 3.5 min. Oxygen consumption (VO(2)) and carbon dioxide production (VCO(2)) were determined as the means of measurements during the last 30 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Indeed, Timmons et al (37) observed in boys that serum levels of testosterone were negatively correlated with fat oxidation during exercise. In obese children and youth, several studies have also shown that the maximal capacity for fat oxidation during exercise is decreased at puberty (38,39). This is concordant with results suggestive of impaired metabolic flexibility.…”
Section: Capacity For Fat Oxidationsupporting
confidence: 64%
“…Indeed, Timmons et al (37) observed in boys that serum levels of testosterone were negatively correlated with fat oxidation during exercise. In obese children and youth, several studies have also shown that the maximal capacity for fat oxidation during exercise is decreased at puberty (38,39). This is concordant with results suggestive of impaired metabolic flexibility.…”
Section: Capacity For Fat Oxidationsupporting
confidence: 64%
“…Pubertal development is an important factor to consider when providing exercise recommendations for obese youth. Both lean and obese boys lower their maximal fat oxidation rates (max FOR) during exercise once they begin puberty (6,36,41,51). Additionally, the exercise intensity at which max FOR occurs (known as FATmax) is less after puberty in boys (36).…”
mentioning
confidence: 99%
“…Similarly, the effect of exercise on fat oxidation has been shown to depend on intensity, duration, and age and body composition of the participants. In this regard, it has been reported that low-tomoderate intensity exercise increases fat oxidation more than does high-intensity aerobic training (12,13); the maximal rate of fat oxidation occurs at a lower percentage of peak oxygen volume (VO 2 peak ) in postpubertal than in pubertal and prepubertal children (14,15); training increased resting fat oxidation in lean adults (16)(17)(18), whereas its influence on resting fat oxidation in overweight and obese adults was inconclusive (6,7,(19)(20)(21). In general, the referenced studies indicate the potential of exercise to increase energy expenditure and fat oxidation.…”
Section: Introductionmentioning
confidence: 99%